Recent Development in Clusters of Rare Earths and Actinides: Chemistry and Materials - Zheng, Zhiping; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
Chemical structure and bonding. The scope of the series spans the entire Periodic Table and addresses structure and bonding issues associated with all of the elements. It also focuses attention on new and developing areas of modern structural and theoretical chemistry such as nanostructures, molecular electronics, designed molecular solids, surfaces, metal clusters and supramolecular structures. Physical and spectroscopic techniques used to determine, examine and model structures fall within the purview of Structure and Bonding to the extent that the focus is on the scientific results obtained and not on specialist information concerning the techniques themselves. Issues associated with the development of bonding models and generalizations that illuminate the reactivity pathways and rates of chemical processes are also relevant. The individual volumes in the series are thematic. The goal of each volume is to give the reader, whether at a university or in industry, a comprehensiveoverview of an area where new insights are emerging that are of interest to a larger scientific audience.
Lanthanide Hydroxide Cluster Complexes via Ligand-Controlled Hydrolysis of the Lanthanide Ions -- Synthesis And Structures of Lanthanide-Transition Metal Clusters.-Hydrothermal Synthesis of Lanthanide and Lanthanide-Transition-Metal Cluster Organic Frameworks via Synergistic Coordination Strategy -- Oxo Clusters of 5f Elements -- Construction and Luminescence Properties of 4f and d-4f Clusters with Salen-type Schiff Base Ligands -- 4f-Clusters for Cryogenic Magnetic Cooling -- Lanthanide Clusters toward Single-Molecule Magnets -- Molecular Rare Earth Hydride Clusters.
Keywords: Inorganic chemistry; Inorganic Chemistry